Selection of materials for natural fibre metal laminates using integrated Cambridge engineering selector and Pugh method - Dhar Malingam, Sivakumar; Mohd Ishak, Noordiana; Ng, Lin Feng; Razali, Nadlene; Ab Ghani, Ahmad Fuad; Siva, Irulappasamy (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
Nowadays, most scientists and manufacturers are looking for lightweight materials to reduce fuel consumption and gas emissions from vehicles to the surroundings. Alternative lightweight materials are highly valued by scientists and manufacturers to reduce gas emission problems. Fibre metal laminates are a new range of lightweight hybrid materials with high levels of fatigue resistance, toughness, strength and energy-absorbing capacity. Natural fibre-reinforced composites have been attracting the attention of scientists and manufacturers as they are biodegradable, environmentally friendly, lightweight and inexpensive. Therefore, the fascinating physical and mechanical properties exhibited by a combination of natural fibre and metal laminates deserve further investigation. This research presents the selection of natural fibre and matrix for natural fibre metal laminates for use in automotive body panels. The material selection was carried out using the Cambridge Engineering Selector software and the Pugh method of analysis. Based on the analysis, kenaf fibre and polypropylene (darified/nudeated) were determined to be the materials that fulfilled the objective constraints of this study, namely, lightweight materials at a minimal cost with maximum performance.